In situ formation of biodegradable dextran‐based hydrogel via Michael addition. Issue 1 (27th April 2012) - Peng, Geng; Wang, Jing; Yang, Fan; Zhang, Shuo; Hou, Juan; Xing, Wanli; Lu, Xun; Liu, Changsheng
Abstract Vinyl‐sulfone‐functionalized dextran (Dex‐VS) was readily prepared by a single‐batch synthetic procedure at room temperature. The thiol molecule, 1, 4‐dithioerythritol (DTE, commercially available) with two terminal thiol groups was used as crosslinking agent. Hydrogels were rapidly prepared in situ by Michael addition under mild physiological conditions. Properties including gelation duration, mechanical modulus, and degradation behavior could be expediently controlled. Moreover, the hydrogels had comparatively low cytotoxicity, and the in vivo tests demonstrated an effective delivery of growth factor. This study might provide a powerful material to be used in tissue regeneration. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012